1998
DOI: 10.1007/s004210050465
|View full text |Cite
|
Sign up to set email alerts
|

Does erythrocyte infusion improve 3.2-km run performance at high altitude?

Abstract: The effects of autologous erythrocyte infusion on improving exercise performance at high altitude have not previously been studied. The effects of erythrocyte infusion on 3.2-km (2-mile) run performance were evaluated during 3 days (HA3) and 14 days (HA14) exposure to high altitude (4300 m) in erythrocyte-infused (ER) and control (CON) subjects that were initially matched (P>0.05; n = 8 in each group) for age, body size and aerobic fitness. After sea-level runs (SL; 50 m), unacclimated-male subjects received e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Are the changes in oxygen tension sensed by endothelial receptors, and is the antagonistic vasoconstriction more pronounced at higher elevations due to a more marked erythropoiesis? This, in addition to other mechanisms suggested by Pandolf et al (1998) may account for the observed lack of bene®t of erythrocyte infusion at more extreme elevations. We hope that these comments stimulate further research and help to advance our understanding of the complicated mechanisms that control oxygen transport in man.…”
Section: Sirsmentioning
confidence: 82%
See 3 more Smart Citations
“…Are the changes in oxygen tension sensed by endothelial receptors, and is the antagonistic vasoconstriction more pronounced at higher elevations due to a more marked erythropoiesis? This, in addition to other mechanisms suggested by Pandolf et al (1998) may account for the observed lack of bene®t of erythrocyte infusion at more extreme elevations. We hope that these comments stimulate further research and help to advance our understanding of the complicated mechanisms that control oxygen transport in man.…”
Section: Sirsmentioning
confidence: 82%
“…(Pandolf et al 1998). I would like to bring to your attention a number of inconsistencies with the original paper and raise some additional points regarding the control of oxygen transport to skeletal muscle.…”
Section: Sirsmentioning
confidence: 94%
See 2 more Smart Citations
“…; Pandolf et al. ). However, these hematological adjustments also have the potential to influence the parameters used to generate the Athlete Biological Passport (Sottas et al.…”
Section: Introductionmentioning
confidence: 98%